Becoming smart? Pursuit of sustainability in urban policy design. Issue 5 (3rd May 2020) - Karppi, Ilari; Vakkuri, Jarmo
ABSTRACT: The pursuit of sustainability through various smart solutions has become prominent in urban policy-making. We explore how cities utilize particular planning and management tools in this endeavour. We introduce the concept of sustainability proxies that are necessities in organizing institutional complexity. We show how that complexity is framed differently from the notorious decision-making silos. This paper provides theoretical accounts to understand the ambiguous nature of sustainability as a target for smart urbanity and scrutinizes the uses of sustainability proxies through an empirical case. The paper provides an account of how public management through proxies actually happens in urban policy-making.